2020
DOI: 10.1016/j.jad.2019.11.110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Thinking Healthy Programme for perinatal depression delivered through peers: Pooled analysis of two randomized controlled trials in India and Pakistan

Abstract: Background:The Thinking Healthy Programme (THP) is recommended to treat perinatal depression in resource-limited settings, but scale-up is hampered by a paucity of community health workers.THP was adapted for peer-delivery (THPP) and evaluated in two randomized controlled trials in India and Pakistan. Our aim was to estimate the effectiveness of THPP on maternal outcomes across these two settings, and evaluate effect-modification by country and other pre-defined covariates.Methods: Participants were pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…One was conducted in Indonesia [68], Timor-Leste [69] and Sri Lanka [70]. One study was conducted in Pakistan and India and their results were pooled [71]. Furthermore, two studies presented different parts of their results in different publications: [44,[61][62][63].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One was conducted in Indonesia [68], Timor-Leste [69] and Sri Lanka [70]. One study was conducted in Pakistan and India and their results were pooled [71]. Furthermore, two studies presented different parts of their results in different publications: [44,[61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…[40] over 12 months, found that a collaborative stepped care intervention resulted in significantly faster recovery rates for anxiety and depressive disorders in public health care patients. THP [41,71] and HAP [49], two promising peer led interventions were both found to reduce levels of depression and depressive remission in India and Pakistan, with HAP also reducing suicidal thoughts or attempts over 12 months in a medium sized RCT in Nepal [64]. A group based peer led life skills intervention [57], a lay counselling intervention [65] and an online behavioural activation programme with peer support [25] were also found to reduce depressive and/or anxiety symptoms at 3, 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low number of studies on psychosocial health in Africa in our review showed that the relationship between perinatal depression/psychosocial health and the role of the male partner is poorly studied in Africa. While some have argued that many low income countries have more pressing issues within maternal health than addressing perinatal depression (such as severe maternal morbidity and mortality)(2), other studies have shown there is reasonable evidence for the benefits and effectiveness of psychological interventions in LMIC(44,47). The low availability of mental health services in LMICs is one of the main challenges for addressing mental health problems, but some recent studies have shown that training and organising lay mental health care workers to address mental health care problems are a feasible and effective approach to combatting mental health disorders(48).…”
Section: Discussionmentioning
confidence: 99%